Penguatan UMKM melalui Pelatihan dan Pendampingan Penerapan Hukum Ekonomi Syariah di Desa Klompang Timur - Hamid, Abd; Adim, Abd.; Febriyanti, Nur Rizka (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in East Klompang Village, Pamekasan still face limitations in understanding and applying the principles of Islamic economic law in business management, particularly regarding transaction practices, financial management, and business ethics. This program aims to improve the understanding and practice of MSMEs in applying the principles of Islamic economic law. The methods used include training, interactive discussions, and practical mentoring The results of the activity indicate an increase in MSMEs' understanding of the basic principles of Islamic economics, such as the prohibition of usury, gharar, and maysir, as well as the importance of fairness and clarity of contracts in transactions. In addition, MSMEs have begun to apply the principles of transparency and fairness in transactions, made improvements in financial management and business marketing, and demonstrated awareness of developing Islamic economic-based businesses. However, obstacles remain, such as limited access to Islamic financial institutions and the use of digital technology. This program shares a positive impact on improving the quality of MSME management, making it more ethical, transparent, and sustainable.